Identifikasi Kesesuaian Atraksi Wisata Pantai Berdasarkan Daya Tampung dan Daya Dukung - Widya Maharani; Yulia Asyiawati (UNISBA Press, 2023)
Abstract. Pangandaran Beach has various kinds of tourist attractions such as beach recreation areas, watersport, swimming, snorkeling, mangrove tourism and camping, but these tourist attractions have not considered the suitability of tourist attractions considering that the Pangandaran beach area is a disaster-prone area, for this reason it is necessary to carry out this study to consider the carrying capacity and carrying capacity of tourist attractions. This study aims to identify the types of tourist attractions in the Pangandaran beach area, identify the suitability of tourist attractions and identify the carrying capacity and carrying capacity of beach tourism attractions in the Pangandaran beach area. The analytical method used is the tourism suitability index, carrying capacity analysis by calculating physical carrying capacity (PCC), real carrying capacity (RCC), and effective carrying capacity (ECC) and regional carrying capacity analysis. Based on the results of the suitability index analysis for beach recreation tourism in the appropriate category (84.52%), mangrove ecotourism (64.10%) and snorkeling tourism (56.14%) in the conditional category, based on the results of calculating capacity, the value of PCC (319,051) > RCC (11,928) > ECC (10,504) shows that the tourism capacity of Pangandaran Beach has not been exceeded. The results of the calculation of the area's carrying capacity can accommodate 65,049 people from all types of tourist attractions. From the results of this analysis, what can be recommended from this study is to develop tourist attractions by adding and updating variations in various kinds of tourist attraction activities. Abstrak. Pantai Pangandaran memiliki berbagai macam atraksi wisata seperti area rekreasi pantai, watersport, berenang, snorkeling ,wisata mangrove dan berkemah akan tetapi atraksi wisata tersebut belum mempertimbangkan kesesuaian atraksi wisata mengingat kawasan pantai pangandaran merupakan kawasan rawan bencana, untuk itu perlu dilakukan kajian ini untuk mempertimbangkan daya tampung dan daya dukung untuk atraksi wisata. Penelitian ini bertujuan mengidentifikasi jenis atraksi wisata yang terdapat di kawasan pantai pangandaran, mengidentifikasi kesesuaian atraksi wisata dan mengidentifikasi daya tampung dan daya dukung atraksi wisata pantai di kawasan pantai Pangandaran. Metode analisis yang digunakan adalah indeks kesesuaian wisata, analisis daya tampung dengan menghitung daya tampung fisik (PCC), daya tampung riil (RCC), dan daya tampung efektif (ECC) dan analisis daya dukung kawasan. Berdasarkan hasil analisis indeks kesesuaian wisata rekreasi pantai kategori sesuai (84,52%), ekowisata mangrove (64,10%) dan wisata snorkeling (56,14%) kategori sesuai bersyarat, berdasarkan hasil pehitungan daya tampung didapatkan nilai PCC (319.051) > RCC (11.928) > ECC (10.504), menunjukan daya tampung wisata Pantai Pangandaran belum terlampaui. Hasil perhitungan daya dukung kawasan dapat menampung 65.049 orang dari seluruh jenis atraksi wisata. Dari hasil analisis tersebut yang dapat direkomendasikan dari kajian ini adalah melakukan pengembangan atraksi wisata dengan penambahan dan pembaharuan variasi dalam berbagai macam aktivitas atraksi wisata.